Morphological elements far a key to subgenera of Bombus Latreille s.l. and Psithyrus Lepeletier s.l. present in Italy (Hymenoptera Apidae Bombinae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The morphological characteristics of the head of the Bombinae, including the genera Bombus Latreille s. l. and Psithyrus Lepeletier s. l. only, have been reviewed and redescribed, by means of the examination of specimens of the species present in Italy. The more significant characteristics have been utilized to draw up some summarizing tables and a dichotomic key, that allow the discrimination of the respective subgenera.
Keywords: Bombus; Psithyrus; morphology; dichotomic key